The design and synthesis of A54556 acyldepsipeptide derivatives and nanomaterials targeting the mycobacterium tuberculosis caseinolytic protease - Cobongela, Sinazo Zezethu Zongeziwe (My University, 2024)
Antibiotics have saved many lives since their discovery in the 1920s, and continue as a first line of defence against microbial infections to date. Unfortunately, their misuse gave rise to the multi-drug resistant (MDR) bacteria that require intensive therapy. Mycobacterium tuberculosis (M. tb) is one of the top pathogens rapidly gaining resistance to current treatment regimens. Over 480 000 cases of MDR tuberculosis (TB) occur every year globally, 9% are caused by the extensively drug-resistant (XDR) M. tb strains. The treatment of MDR/XDR-TB is long, toxic and expensive, and the success rate is largely unsatisfactory. Hence, there is an urgent need for new and effective anti-TB drugs. Over the years, peptide based therapeutics have been used and were successful in treatment of various diseases such as TB, cancer, cardiovascular diseases, diabetes and others. Due to the instability, poor solubility and toxicity of natural antimicrobial peptides (AMPs), great attention is now focussed towards synthetic analogues of the AMPs to improve their pharmacokinetics. One of the new antibacterial targets that have gained traction over the years is the proteolytic regulating protease called Caseinolytic protease (ClpP). ClpP degrades misfolded and aggregated proteins and peptides that have potential to induce toxicity within the bacterial cell. ClpP can be indirectly targeted by dysregulating ClpP-ATPases such as ClpC1 and ClpX, which are responsible for activation of the ClpP proteolytic activity. Acyldepsipeptides (ADEPs) function by mimicking the binding of ClpP-ATPases to ClpP, thereby inducing nonselective proteolysis, which ultimately leads to bacterial death. Due to the essential role played by ClpP in the biology of the M. tb, thus ADEPs are regarded as potential antibiotics with a novel mechanism to combat the bacterial resistance problem. However, ADEPs also have limitations such as poor membrane permeability and high cytotoxicity. Therefore, the aim of this study was to design and synthesise biocompatible ADEP1 analogues as potent antibacterial agents, and to improve their membrane permeability and efficacy by conjugating the analogues to Silver/Indium/Sulphide (AgInS2) quantum dots (QDs) as nano-carriers. Twenty cyclic ADEP1 analogues were designed and synthesised using the solid phase peptide synthesis (SPPS) strategy. Four of the ADEP1 analogues were conjugated to the AgInS2 QDs, and characterised with UV-Vis, Spectro Xepos05 energy-dispersive X-ray fluorescence, highresolution transmission electron microscope, and spectrofluorophotometer. The antibacterial activity of the ADEP1 analogues and AgInS2 QDs-ADEP1 analogue conjugates was tested against two Gram-negative bacteria, Escherichia coli (E. coli) and Pseudomonas aeruginosa vi (P. aeruginosa), and three Gram-positive bacteria, Bacillus subtilis (B. subtilis) and Staphylococcus aureus (S. aureus), including Methicillin-resistant Staphylococcus aureus (MRSA). The biocompatibility and cytotoxicity effects of the ADEP1 analogues and AgInS2 QDs-ADEP1 analogue conjugates was evaluated on HEK-293 and Caco-2 cells using the MTS viability assay. The effect of the ADEP1 analogues on the peptidase activity of the M. tb ClpP1P2 was investigated. The aqueous solubility and membrane permeability of the ADEP1 analogues was investigated using the MultiScreen aqueous solubility assay and the Parallel Artificial Membrane Permeability Assay (PAMPA), respectively. Four of the ADEP1 analogues were successfully synthesized by SPPS with >96% purity and >36% yield. Both the ADEP1 analogues and AgInS2 QDs-ADEP1 analogue conjugates showed potency against Gram-positive and Gram-negative bacteria, however, the efficacy of the ADEP1 analogues was significantly enhanced when conjugated to the AgInS2 QDs. In Gram-positive bacteria, the ADEP1 analogues exhibited a minimum inhibition concentration (MIC) ranging from 63-125 µM while the AgInS2 QDs-ADEP1 analogue conjugates had lower MIC values (9.38-18.75 µM). The MIC values of ADEP1 analogues against Gram-negative bacteria were between 125 and 500 µM while the AgInS2 QDs-ADEP1 analogue conjugates had MICs between 2.34 and 37.5 µM. Both the unconjugated peptides and conjugates showed minimum bactericidal concentrations (MBC) twice their MIC. In addition, the ADEP1 analogues and AgInS2 QDs-ADEP1 proved to be biocompatible as they were non-toxic to the cells. The ADEP1 analogues further showed moderate aqueous solubility and gastrointestinal membrane permeability. Furthermore, the effect of the ADEP1 analogues on the peptidase activity of the M. tb ClpP1P2 protease was investigated. All the analogues enhanced M. tb ClpP1P2 activity. Of the four ADEP1 analogues that were tested, SC008 and SC005 showed activation percentages that were 32% and 14% higher than benzoyl-leucyl-leucine (Bz-LL), a known ClpP1P2 activator, respectively. These results suggested the potential use of these novel ADEP1 analogues as leads in the development of broad spectrum anti-bacterial agents. The ADEP1 analogues also demonstrated potential anti-mycobacterium activity by activating M.tb ClpP1P2. The mode of action followed by the ADEP1 analogues is an interesting finding that can be explored to develop new and effective antibacterial drugs with potential to eradicate drug resistance. Therefore, future studies warrants investigation of the anti-TB effects and molecular mechanism of the ADEP1 analogues and conjugates in in vitro and in vivo models of M.tb.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023
Keywords: Mycobacterium tuberculosis; Antibiotics; Microbial infections